Entrepreneurial attitude, geographical isolation and university students - some evidence from the Atlantic - António Almeida; Jo\~ao Andrade; Jo\~ao Freitas; Isabel Martins (European Regional Science Association (ERSA), 2005)
Some regions like Island of Madeira show high levels of firm birth rate. But the entrepreneurial experience is quite different from the European reality given the high level of micro-business owing o subsistence reasons, as a response to the reduced opportunity costs, the lack of profitable employment options and the high levels of unemployment. As a consequence the high level of entrepreneurship is only partially related to high tech innovative firms, qualified employment growth and economic diversification. The majority of the new firms are linked with traditional sectors (restaurants, boutiques, personal services and civil construction. Firm creation is also a result of the EU integration and cohesion policies. On the other hand infra-structure development policies explain the increasing importance of the public administration in terms of employment and consequently the low levels of unemployment. Traditionally, in the islands, the government intervention in terms of employment, economic planning is considered excessive. The island economies have been able to benefit from large streams of international solidarity in terms of high external aid per capita especially due to their strategic relevance. But the global economic and political change associated with the globalisation put increasing pressure on the island forcing them to reformulate their economic, social and political options. International donors and institutions like World Bank stresses issues such as economic diversification, economic and social modernisation and macroeconomic policies focused o supply side effects and the development of economic growth determining factors. Due to the reduced levels of international aid, islands are obliged to diminish levels of government intervention connected to public employment and direct production activities and to enhance private initiatives and entrepreneurship. In what concerns the outermost regions the EU enlargement demands increasing levels of competitivity, financial autonomy, economic diversification and entrepreneurial attitude. Given the lack of studies in this geographical area, the on-going economic, social and cultural modernisation induced by the integration in The EU sphere and the widespread perception about the changing times, we intend in this study to give some answers to the following questions: .how is the entrepreneurial attitude affected by the historical record of high levels of government intervention and public employment? .what kind of impacts results from the perceived "island penalty”, in terms of propensity towards entrepreneurship? .What is the main obstacle to the entrepreneurial event? .Should one wish to create a firm, what is the probability of the stated preference is in the high tech sectors? What kind of support will be required and welcomed from the public institutions? Studies and academic studies in islands have some advantages. The agglomeration of institutions, populations, firms and social networks in a reduced geographical space enable us to capture in some detail a vast group of variables, relationships and cause effects linked to a specific subject. Islands societies have a large and cohesive social capital, and share a homogenous set of values and cultural attitudes, which facilitates experiences of collective action. To conduct an empirical test in order to find out the most influential variables in the entrepreneurship attitude we use logit equations. The sample is made up of local university students, theoretically the most apt in developing innovative firms. We investigate also the differences between economics and managements and humanities students in terms of entrepreneurship propensity. An important matter in isolated, peripheral and underdeveloped regions is the diffusion of innovations. Consequently, student's sources of information and knowledge regarding the overall tendencies of profitable, innovative and fashionable entrepreneurial experiences must be identified. Therefore, this paper describes the changing and uncertain economic and political environment faced by islands societies. A contextualisation of the relationship between entrepreneurship, economic growth and insular penalty is stretched and lastly, we provide an empirical study related to the entrepreneurial attitude in an insular region: The Island of Madeira.
Keywords: 330